UPAYA GURU DALAM MENINGKATKAN MOTIVASI SISWA PADA PEMBELAJARAN BAHASA INGGRIS DI MADRASAH IBTIDAIYAH AL KHAIRIYAH BANJARBARU - Istiqomah Istiqomah; Ahmad Nazif (Program Studi PGMI STAI Al Falah Banjarbaru, 2019)
This study discusses the efforts of teachers in increasing student motivation in learning English in Madrasah Ibtidaiyah Al Khairiyah Banjarbaru. The purpose of this study was to determine how the teacher's efforts to improve student motivation in learning English in Madrasah Ibtidaiyah Al Khairiyah Banjarbaru and what are the factors that influence it. The type of research the author does is the type of field research (field research) using a qualitative approach. For data mining, the writer uses observation, interview, and documentation techniques. While the data processing technique is done by editing, data classification, and data interpretation. Subsequently analyzed descriptively qualitatively and concluding by inductive. The results showed that the teacher's efforts in increasing student motivation in learning English in the Al Khairiyah Ibtidaiyah Madrasah were quite good. Student motivation in learning English can be influenced by several factors, namely the level of student awareness of the need to learn English, the teacher's attitude toward class, the influence of student groups, class atmosphere, and the completeness of learning support facilities. Keywords: Teacher Efforts, Learning Motivation, Madrasa Students, English.